2021
DOI: 10.1016/j.jceh.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Admission Serum Urea is a Better Predictor of Mortality than Creatinine in Patients With Acute-On-Chronic Liver Failure and Acute Kidney Injury

Abstract: Background: The occurrence of acute kidney injury (AKI) in acute-on-chronic liver failure (ACLF) negatively impacts the survival of patients. There are scant data on the impact of serum urea on outcomes in these patients. We performed this study to evaluate the relationship between admission serum urea and the survival in patients with ACLF and AKI. Methods: A prospective study was conducted on patients with ACLF (as per Asian Pacific Association for the Study of the Liver criteria) and AKI (as per Acute Kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In patients with acute kidney injury, it is possible to find fluid overload from the initial stages [79], which means that in severe cases that do not respond to fluid restriction and the use of diuretics, renal replacement therapy is indicated [80,81]. For this reason, the association between high urea values and higher mortality in patients with acute kidney injury [82,83] could explain our findings. However, the presence of high BAR values in patients without the severe disease can be explained by the units of measurement used or the dilution of urea values caused by fluid overload, similarly to what happens with the serum creatinine [84,85].…”
Section: Discussionmentioning
confidence: 70%
“…In patients with acute kidney injury, it is possible to find fluid overload from the initial stages [79], which means that in severe cases that do not respond to fluid restriction and the use of diuretics, renal replacement therapy is indicated [80,81]. For this reason, the association between high urea values and higher mortality in patients with acute kidney injury [82,83] could explain our findings. However, the presence of high BAR values in patients without the severe disease can be explained by the units of measurement used or the dilution of urea values caused by fluid overload, similarly to what happens with the serum creatinine [84,85].…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, acute kidney injury is an important predictor of early mortality in patients ACLF 38 . A study has indicated that serum urea is a more accurate predictor of mortality than serum creatinine in ACLF patients with acute kidney injury 39 . In critically ill patients, an elevated BUN was associated with increased mortality independent of serum creatinine 40 .…”
Section: Discussionmentioning
confidence: 99%